Pencarian Rekognisi dan Legalitas Perkawinan Secara Adat Pada Suku Asli Anak Rawa di Siak Provinsi Riau - Ansor, Muhammad; Alwi, Rahman; Zulfikar, Irfan; Masyhur, Laila Sari; Alit, Alit (Program Pascasarjana IAIN Langsa, 2023)
This article deals with the search for the recognition and legality of customary marriages on believers of the Suku Asli Anak Rawa in Siak, Riau. The article argued that although the Constitutional Court ordered the writing of identity credentials on the residence documents of citizens of trust holders, it could not be realized because they did not have a trust organizations or holders of trusts. This resulted in a number of Suku Asli Anak Rawa convert to one of the state-recognized religions in order to obtain a document of identity. Ethnographic data was collected through in-depth interviews, semi-structured observations as well as document studies. First, the author explores the indigenous population of the Anak Rawa who still embrace their beliefs and compares them to citizens who have converted to one of the official religions. Second, the researchers explored patterns of strengthening the external social networks of Suku Asli Anak Rawa, both government agencies and relevant social organizations as part of identity strengthening and search for recognition over indigenous marriages. Third, the researchers explored the efforts made by the Suku Asli Rawa in filing a registered status application to have the legality of issuing a marriage certificate. In conclusion, this paper indicates that policy on religious minority groups cannot be implemented immediately because of the limited capacity of citizens to meet administrative demands and bureaucratic processes in government.